Cognitive impairment in the population-based ural very old study - Bikbov, Mukharram; Kazakbaeva, Gyulli M.; Iakupova, Ellina M.; Panda-Jonas, Songhomitra; Fakhretdinova, Albina A.; Tuliakova, Azaliia M.; Rusakova, Iuliia A.; Jonas, Jost B. (Frontiers in aging neuroscience, 2022)
BackgroundDespite its marked importance in public health, the prevalence of cognitive impairment (CI) and its associated factors have only rarely been examined in old populations in general or in Russia at all.ObjectiveTo assess CI prevalence and its determinants in a very elderly population in Russia.Materials and methodsThe population-based Ural Very Old Study, conducted in rural and urban region in Bashkortostan/Russia, included 1,526 (81.1%) out of 1,882 eligible individuals aged 85+ years. A series of medical examinations including the Mini-Mental State Examination (MMSE) for the assessment of CI was performed.ResultsMini-Mental State Examination data were available for 1,442 (94.5%) individuals (mean age: 88.3 ± 2.9 years; range: 85-103 years). The median MMSE score was 24 (interquartile range: 19, 27). Prevalence of any CI (MMSE score < 24 points) was 701/1,442 [48.6%; 95% confidence interval (CI): 46.0, 51.2]. Prevalence of mild, moderate and severe CI (MMSE score 19-23 points, 10-18 points, and ≤9 points, respectively) was 357/1,442 (24.8%; 95% CI: 22.5, 27.0), 246/1,442 (17.1%; 95% CI: 15.1, 19.0), and 98/1,442 (6.8%; 95% CI: 5.5, 8.1), resp. A lower MMSE score correlated (regression coefficient r2: 0.31) with older age (beta: −0.13; P < 0.001), rural region of habitation (beta: 0.15; P < 0.001), lower level of education (beta: 0.19; P < 0.001), higher depression score (beta: −0.33; P < 0.001) (or alternatively, higher prevalence of hearing loss (beta: −0.10; P = 0.001), worse visual acuity (beta: −0.10; P = 0.001), and lower physical activity (beta: 0.06; P = 0.04).ConclusionIn this elderly study population from rural and urban Russia, prevalence of any, mild, moderate and severe CI was 48.6, 24.8, 17.1, and 6.8%, resp. Besides medical and lifestyle factors, vision and hearing impairment were major factors associated with CI.
Gesehen am 20.12.2022